Exploring Proactive Career Behavior Questionnaire Psychometrics Properties: An Adaptation to Spanish Distance Undergraduate Students - Miguel Bernabé; Richard Merhi; Ana Lisbona; Francisco Palací (SAGE Open)
Proactivity about a professional career predicts the employability of students in the job market. Having a scale will facilitate research and intervention using proactive behaviors. The objective of the present study is to adapt the Proactive Career Behavior questionnaire in Spanish distance university students. To that end, the questionnaire is administered to 934 undergraduates. The factorial structure, validity and reliability of the questionnaire are analyzed, as well as the invariance of the scale as a function of gender. The current study demonstrates that the Spanish questionnaire was found to be a reliable and valid measure of proactive career behavior of distance undergraduates. The same number of items and the tetra-factorial structure of the original are maintained. The original structure shows to be invariant across gender. The Spanish version of the questionnaire has adequate psychometric properties. Reliability is high and validity is right. The hypothesized relationships between constructs are supported. The Spanish adaptation shows reliable and valid outcomes for both genders, with resilience, personal initiative, and future orientation correlating with students’ proactive career behaviors.